E -money as a key tool to promote financial inclusion - Ramos Zaga , Fernando Antonio (2023)
Financial inclusion in Peru faces considerable difficulties due to low levels of access to financial services such as loans and savings accounts. To address this challenge, electronic money emerges as a tool that could potentially reach populations underserved by traditional banking. Therefore, the widespread use of mobile telephony in Peru is essential to promote financial inclusion in economically vulnerable populations. In this sense, the objective of this article is to analyze the legal framework of electronic money, as well as the barriers to access in the supply and demand of financial services. It concludes that e-money can bring essential financial services to previously underserved populations, taking advantage of the existing mobile infrastructure.